Recovery of Hydroxytyrosol from Olive Mill Wastewater Using the Promiscuous Hydrolase/Acyltransferase PestE. (31st May 2022) - Terholsen, Henrik; Kaur, Jasmin; Kaloudis, Nikolaos; Staudt, Amanda; Müller, Henrik; Pavlidis, Ioannis V.; Bornscheuer, Uwe T.
Abstract: Olive mill wastewater (OMWW) is produced annually during olive oil extraction and contains most of the health‐promoting 3‐hydroxytyrosol of the olive fruit. To facilitate its recovery, enzymatic transesterification of hydroxytyrosol (HT) was directly performed in an aqueous system in the presence of ethyl acetate, yielding a 3‐hydroxytyrosol acetate rich extract. For this, the promiscuous acyltransferase from Pyrobaculum calidifontis VA1 (PestE) was engineered by rational design. The best mutant for the acetylation of hydroxytyrosol (PestE_I208A_L209F_N288A) was immobilized on EziG 2 beads, resulting in hydroxytyrosol conversions between 82 and 89 % in one hour, for at least ten reaction cycles in a buffered hydroxytyrosol solution. Due to inhibition by other phenols in OMWW the conversions of hydroxytyrosol from this source were between 51 and 62 %. In a preparative scale reaction, 13.8 mg (57 %) of 3‐hydroxytyrosol acetate was extracted from 60 mL OMWW. Abstract : Use it all : Olive mill wastewater contains the majority of health‐promoting olive phenols, but this resource has been little utilized. For the valorization of olive mill wastewater, the promiscuous acyltransferase PestE was engineered to acetylate hydroxytyrosol notably in an aqueous phase and to facilitate its extraction into the organic ethyl acetate phase.